Affective spectrum disorders and role of serotonergic system of the brain - Timotijević Ivana P.; Todorović Mirjana M.; Crnic Katarina B.; Marković Srđan Z.; Kastratović Dragana A. (Srpsko lekarsko drustvo, 2014)
Affective spectrum disorders include mood and anxiety disorders, whereas the term functional somatic syndromes describes disorders in which the main symptom is chronic pain, with no pathognomonic tissue damage, such as fibromyalgia, irritable colon, tension headache. Pain as a symptom is often present in patients with depression and anxiety, and similarly, depressed mood, anxiety and other psychiatric symptoms are common in patients with functional somatic syndromes. This explains attitudes that affective disorders and functional somatic syndromes should be found along the same spectrum, due to a similar neurobiochemicalmehanism and dysfunction of these CNS structures and neurotransmitter systems, which lead to similar symptoms in both groups. The symptoms of affective disorders, including somatic are associated with serotonin and serotonergic transmission in the CNS. The existence of depressive and anxiety disorders, such as fatigue, sleep disorders, cognitive disorders, depressed mood, anxiety, and functional somatic syndromes code indicate a similar mechanism of origin. Hypothesis of central neuropathic pain explains the possibility of the descending inhibitory pain mechanisms, including serotonergic and noradrenergic projections and their receptors. Central suprasegmental senzitization in nociceptive pathways, also at the level of the thalamus and the sensory cortex, trigered by an emotional stressors can cause painful symptoms in both groups of disorders. Serotonergic and noradrenergic pathways and voltage sensitive channels of their receptors are included in the mechanism. Modern psychopharmacology can no longer ignore the existence of painful symptoms in affective disorder or depressive and anxiety symptoms in functional somatic syndromes and their treatment can improve. Therapeutic effects of SSRI and SNRI antidepressants and alpha 2 delta ligands for all kinds of painful symptoms in affective disorders - serotonergic spectrum is expected, due to the impact of the dysfunctional neurotransmission in specific regions of the CNS, increasing the efficiency of information processing and reduction of symptoms.